(untitled) (Canadian Medical Education Journal, 2025)
Implication Statement Clinical reasoning and associated clinical decision-making (CDM) skills are crucial to determining an accurate diagnosis and appropriate management plan. Medical trainees are intended to learn these skills in the clinical environment, yet these settings are inherently variable leading to gaps in clinical cases encountered. Selecting and incorporating meaningful clinical scenarios with active student participation help address variability in clinical encounters necessary to enhance learning CDM. Expanding CDM sessions using key feature questions (KFQs) and a team-based learning (TBL) approach could address clinical encounter gaps and continued development of CDM skills across clerkships.